2021
DOI: 10.1186/s13023-021-02138-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health diagnoses in adults with phenylketonuria: a retrospective systematic audit in a large UK single centre

Abstract: Background Recently published European Society for Phenylketonuria (ESPKU) guidelines have recommended a lifelong diet with phenylalanine (Phe) control ≤ 600 μmol/L for phenylketonuria (PKU) patients. This study aimed to identify whether PKU adult patients are at a higher risk of mental health diagnoses if their 2-year average Phe level is higher than the ESPKU European guidelines. Published studies identified by a literature review showed that related studies have been published in American an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, opposite conclusions have been published elsewhere [ 39 ] and hence, the safety of treatment targets in PKU will remain a matter of debate until a larger portion of adults with PKU are able to achieve and maintain blood Phe concentrations below at least 600 µmol/L with available treatment options. Despite disagreement on the safety of the upper blood Phe target, it is clear that even in adulthood, blood Phe concentrations above 600 µmol/L are detrimental to mental health outcomes (e.g., anxiety) and executive function, complicating the planning of low-protein meals and impacting the ability to schedule in-clinic appointments, which for some leads to a cycle of suboptimal treatment adherence [ 15 , 26 , 41 , 47 , 48 ]. Statement #7 Consensus Due to the sustainability challenges related to MNT, adults with PKU should be offered pharmacological treatments to lower blood Phe levels when available.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, opposite conclusions have been published elsewhere [ 39 ] and hence, the safety of treatment targets in PKU will remain a matter of debate until a larger portion of adults with PKU are able to achieve and maintain blood Phe concentrations below at least 600 µmol/L with available treatment options. Despite disagreement on the safety of the upper blood Phe target, it is clear that even in adulthood, blood Phe concentrations above 600 µmol/L are detrimental to mental health outcomes (e.g., anxiety) and executive function, complicating the planning of low-protein meals and impacting the ability to schedule in-clinic appointments, which for some leads to a cycle of suboptimal treatment adherence [ 15 , 26 , 41 , 47 , 48 ]. Statement #7 Consensus Due to the sustainability challenges related to MNT, adults with PKU should be offered pharmacological treatments to lower blood Phe levels when available.
…”
Section: Resultsmentioning
confidence: 99%
“…There is consensus that patients with PKU should avoid elevations in blood Phe throughout life to preserve neurotransmitter production and myelin synthesis [ 1 , 2 , 3 ]. Although the neurotoxic effects of Phe seem to vary between individuals, there is a general trend of increased vulnerability to mental health disorders, including mood disturbances, anxiety and depression, correlated with blood Phe concentrations in adulthood [ 15 , 21 , 42 , 48 , 91 , 92 , 93 , 94 ]. However, in some studies, the relationship between biochemical markers and neuropsychological symptoms was not significant [ 95 , 96 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that mood alterations, such as anxiety and depression, are more prevalent in PKU patients, particularly in those with higher phenylalanine concentrations than recommended [ 10 , 23 ]. In the present study, angry/irritable mood was the most frequent unfavorable symptom reported in all age groups, followed in the order of frequency by failure to concentrate/difficulty in focusing and sad mood in pediatric group; failure to concentrate/difficulty in focusing and difficulty in understanding the subjects in the class/at work/daily life in the adolescent group; feeling of tiredness and failure to concentrate/difficulty in focusing in the adult group.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 39 articles, neurological signs and symptoms were present in adults who were early diagnosed and treated, particularly if they discontinued treatment after childhood [25]. Adults may also have impairments of reasoning, visual-spatial attention, processing speed, sustained attention, visuo-motor control, inhibitory control, working memory and cognitive flexibility [22,26,27] and increased risk of emotional and behaviour deficits (e.g., attention deficit, hyperactivity, depression, anxiety, low mood, mood swings, poor self-image, withdrawal, and a lack of autonomy and drive) [23,28,29]. Psychiatric symptoms such as panic disorders and agoraphobia are reported [30].…”
Section: Introductionmentioning
confidence: 99%
“…European and American guidelines on the management of PKU recommend maintenance of blood Phe levels in the therapeutic target range of: Europe: 120-360 µmol/L in patients <12 years of age and 120-600 µmol/L in patients ≥12 years; USA: 120-360 µmol/L in all age groups [5,35]. However, blood Phe control deteriorates with age, and most adult patients cannot maintain blood Phe control within target ranges (i.e., blood Phe levels exceeding 600 µmol/L) [29,[36][37][38][39]. Some adults may partially follow dietary treatment, commonly without a Phe-free/low-Phe protein substitute.…”
Section: Introductionmentioning
confidence: 99%